Analysis of City Branding and Smart City on The Decision to Visit Geopark Ciletuh Sukabumi - Sulistiana, Alivia; Sudarma, Ade; Siwiyanti, Leonita (Lafadz Jaya Publisher, 2024)
This study aims to analyze city branding and smart city on the decision to visit Ciletuh Geopark, Sukabumi Regency. The method used in this study is a quantitative descriptive method. The results of this study indicate that City Branding has an effect on City Image, Smart City has a positive effect on City Image, City Image has an effect on the decision to visit, meaning that the better the City Branding that is implemented, the more it will increase the visitor's decision to visit Ciletuh Geopark, City Branding has no effect on the decision to visit, and Smart City has an effect on the decision to visit. This study contributes to the development of marketing management science, especially in the field of city branding and smart city in the tourism industry. The results of this study emphasize the importance of applying these concepts to improve visitor experience and satisfaction, and offer additional insights on how to optimize destination marketing strategies through technological innovation and more effective branding approaches.